The Fear of Losing—Nonsuicidal Self-Injury as a Protective Mechanism in Eating Disorders - Sagiv, Eran; Hadlaczky, Gergö; Sheetrit, Noga; Gur, Eitan; Horesh, Netta; Gvion, Yari (Frontiers in Psychiatry, 2019)
Background: This study examined the moderating role of loss aversion (LA) on the relationship between impulsivity, non suicidal self-injury (NSSI), suicidal attempts and ideations among Eating Disorder (ED) patients. Methods: Data was collected on 81 ED patients and 37 healthy controls. ED patients were divided into 2 groups: 25 AN-Rs, 56 AN-BPs and BNs. Measurements of trait impulsivity, LA, NSSI, suicide attempts and suicide ideations were collected. Results: The rate of attempting suicide was highest in the AN-BP/BN (34.8%), lower in the AN-Rs (8%) and the lowest in the controls (2.7%). Suicide ideation was also higher in AN-BP/BN compared to both AN-R and controls. NSSI was higher in the AN-BP/BN group compared to both AN-R and control groups. LA scores were lower among participants with EDs compared to controls. BMI and depression were positively associated with suicide ideation and NSSI. Impulsivity was associated to suicide attempt and suicide ideation. Contrary to our hypothesis, LA scores were positively correlated with NSSI and SI. A stepwise regression revealed that contradictory to our hypothesis, higher LA predicted NSSI prevalence severity of NSSI and suicide ideation. Limitations: (1) Cross-sectional design; (2) Relatively small sample size of clinical subjects and only female participants; (3) Heterogeneity of treatment status. Conclusions: EDs are associated with lower levels of LA compared to general population. Although high LA is considered a protective factor against “high damage” decisions, it may serve as a facilitator of lower risk decisions which help the individual soothe and communicate his or her own suffering such as NSSI.